1992
DOI: 10.2136/sssaj1992.03615995005600060025x
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Fraction Organic Matter in Soils from Long‐Term Crop Rotations

Abstract: Light-fraction (LF) material, comprised largely of incompletely decomposed organic residues, may provide a sensitive indicator of the effects of cropping practices on soil organic matter. The objective of our study was to determine the influence of agronomic variables on soil LF content, and to evaluate the LF as a measure of labile organic matter. Soils from three long-term crop rotation studies in Saskatchewan, Canada, were analyzed for LF content and composition. The experiments, established at Indian Head … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

33
281
1
26

Year Published

1998
1998
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 620 publications
(341 citation statements)
references
References 0 publications
33
281
1
26
Order By: Relevance
“…Similar results were reported by Nyborg et al ( , 1999. The LFOC is important for soil organic matter turnover, because it is a readily decomposable substrate for microorganism and a source of plant nutrients ; it is associated with larger micorbial population (Kanazawa and Philips 1986) and activity (Janzen et al 1992). For example, loss of organic C from the light fraction was 2 to 11 times greater than that from the heavy fraction in five Australian soils (Dalal and Meyer 1986) and >70% of LFOC had turned over compared to 16% of C associated with the coarse silt fraction since the start of maize cropping in an Ontario soil (Gregorich et al 1995).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Similar results were reported by Nyborg et al ( , 1999. The LFOC is important for soil organic matter turnover, because it is a readily decomposable substrate for microorganism and a source of plant nutrients ; it is associated with larger micorbial population (Kanazawa and Philips 1986) and activity (Janzen et al 1992). For example, loss of organic C from the light fraction was 2 to 11 times greater than that from the heavy fraction in five Australian soils (Dalal and Meyer 1986) and >70% of LFOC had turned over compared to 16% of C associated with the coarse silt fraction since the start of maize cropping in an Ontario soil (Gregorich et al 1995).…”
Section: Resultssupporting
confidence: 80%
“…Total N was determined by digesting the soil samples in concentrated sulphuric acid, followed by determination of NH 4 in the digest using a Technicon AutoAnalyser II (Technicon Industrial Systems 1977). Light fraction organic matter (LFOM) was separated using Na1 solution of 1.7 Mg m -3 specific gravity following the method described by Janzen et al (1992) and modified by Izaurralde et al (1997). The LFOC and LFN in LFOM were measured by Dumas combustion using a Carlo Erba elemental analyzer (Model NA 1500, Carlo Erba Strumentazione, Italy).…”
Section: Methodsmentioning
confidence: 99%
“…Pelos resultados, constata-se que as frações leves podem vir a ser utilizadas como indicadores de alterações resultantes do manejo do solo. Estes resultados concordam com os de outros estudos (Dalal & Mayer, 1986;Janzen et al, 1992), em que as frações mais lábeis da MOS, como a fração leve, têm-se apresentado como um indicador sensível às mudanças decorrentes das diferentes formas de uso do solo. Nas figuras 4 e 5, encontram-se os teores totais de C e N nas frações leves.…”
Section: Resultsunclassified
“…As frações leves da matéria orgânica foram obtidas pelo procedimento proposto por Sohi et al (2001). As frações leves (Figura 1) foram extraídas do solo por meio de uma solução de NaI a uma densidade de 1,80 g cm -3 (± 0,02), conforme sugerido por Janzen et al (1992). Os métodos tradicionais de separação da fração leve normalmente utilizam soluções com densidade ajustada para 2,0 g cm -3 , porém, neste estudo, adotou-se uma densidade menor, por dois motivos: 1) permite o uso de soluções inorgânicas, que oferecem vantagens em termos de segurança e conveniência sobre as orgânicas; 2) evita a contaminação da fração leve com partículas minerais, que apresentam densidade de 2,0 g cm -3 .…”
Section: Methodsunclassified
“…The free light fraction of organic matter was obtained by the procedure proposed by SoHi et al (2001), as suggested by Janzen et al (1992). The quantification of total glomalin, a glycoprotein found in mycorrhizal fungi, was performed using the test of BraDForD (1976), modified by wrigHt and upaDHyaya (1998).…”
Section: Methodsmentioning
confidence: 99%